2009
DOI: 10.1002/jcp.21939
|View full text |Cite
|
Sign up to set email alerts
|

Candida famata modulates toll‐like receptor, β‐defensin, and proinflammatory cytokine expression by normal human epithelial cells

Abstract: Candida albicans is no longer the only yeast involved in infectious disorders, as others, such as C. famata, commonly associated with foods as well as terrestrial and marine environments, are being recognized as potential emerging pathogens that cause human candidiasis. We investigated the interaction between C. famata and human epithelial cells using monolayer cultures and an engineered human oral mucosa (EHOM). C. famata was able to adhere to gingival epithelial cells but failed to adopt the hyphal form in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 60 publications
1
29
0
3
Order By: Relevance
“…For example, in response to Candida parapsilosis, human gingival epithelial cells upregulate TLRs and antimicrobial peptides, such as hBD-1 (human ␤-defensin 1) and hBD-2, to inhibit fungal growth (5). Similar results were also observed when Candida famata was used to stimulate oral epithelial cells (6).…”
Section: Cell Types Involved In Host Innate Defenses Against Candida mentioning
confidence: 68%
“…For example, in response to Candida parapsilosis, human gingival epithelial cells upregulate TLRs and antimicrobial peptides, such as hBD-1 (human ␤-defensin 1) and hBD-2, to inhibit fungal growth (5). Similar results were also observed when Candida famata was used to stimulate oral epithelial cells (6).…”
Section: Cell Types Involved In Host Innate Defenses Against Candida mentioning
confidence: 68%
“…Abbreviations: PaCO 2 = arterial carbon dioxide tension; MODS: Multi-organ Dysfunction Syndrome; Other abbreviations see the text. [28,29], generated by stressed host cells, or exogenous pathogen-associated molecular patterns (PAMPs) [30][31][32] are recognized as being capable of activating the pattern recognition receptors (PRRs) [33] of the immune cells and as promoting the synthesis of inflammation mediators. Thus, any kind of tissue damage (pathogens [34,35], CRT [8,9] etc.)…”
Section: Deteriorating Evolution Of Systemic Inflammationmentioning
confidence: 99%
“…Gingival epithelium is in direct contact with the environment and functions as a physical barrier against bacterial invasion when periodontal pathogenic bacteria stimulated gingival epithelia, inflammatory and anti-inflammatory cytokines are produced [23] [24]. Cubitt et al reported IL-1RII mRNA expression in corneal epithelial cells, which was enhanced by stimulation with the inflammatory cytokines IL-1α and TNF-α [25].…”
Section: Discussionmentioning
confidence: 99%